Numerical Study of Singularity Formation in Relativistic Euler Flows (Communications in Computational Physics, 2014)
The formation of singularities in relativistic flows is not well understood.Smooth solutions to the relativistic Euler equations are known to have a finite lifespan;the possible breakdown mechanisms are shock formation, violation of the subluminalconditions and mass concentration. We propose a new hybrid Glimm/central-upwindscheme for relativistic flows. The scheme is used to numerically investigate,for a family of problems, which of the above mechanisms is involved.